Relación entre los ingresos y gastos públicos del Gobierno Regional de Loreto del periodo 2013 al 2022 - Ferry Lozano, Jhenifer Jhonely (2024)
The general objective of this study was to determine the relationship between public income and expenses of the regional government of Loreto from the period 2013 to 2022. For this reason, the following method was carried out: quantitative type and non-experimental design since the variables will not be manipulated variables. It is a correlational study because it measures the relationship in statistical terms. The results were: The coefficient of determination R2 had a value of 0.87434316, which is close to 1, accepting the general hypothesis where it is stated that: There is a direct relationship between the public income and expenses of the regional government of Loreto from the period 2013 to 2022. Also, specific hypotheses 1 and 2 are accepted where it is stated that: The behavior of both the income and public expenses of the regional government of Loreto is increasing from the period 2013 to 2022. This is supported by the results found: Income Public for the year 2013 was S/ 394,751,848 and for the year 2022 it increased to S/.1,164,264,797, which were mostly from the Determined Resources. Public Expenditure for the year 2013 was S/. 1,210,256,261 and in 2022 it increased to S/.2,856,120,511 from Ordinary Resources. Finally, specific hypothesis 3 is rejected: The level of correlation between public income and expenses of the regional government of Loreto from the period 2013 to 2022 is acceptable, since the Correlation Coefficient had the value of 0.93506319, which indicates it is “excellent” since which is between 0.90 and less than 1.